(untitled) (International Seven Journal of Multidisciplinary, 2025)
The aim of this work was to analyze the biological indicators of the soil in areas where grain, soy and corn are grown in the region of Santarém, Mojuí dos Campos and Belterra Pará. The analyses were carried out using BioAS technology, developed by EMBRAPA Cerrado. Through enzyme activity, it is possible to access the soil memory associated with the non-living fraction accumulated in the protected soil, through absorption in clay particles and organic matter. Soil samples were collected from four areas: Tapajós National Forest - FLONA (very clayey texture), Novo Horizonte Farm (very clayey texture) and two areas on Texa Farm (clayey and medium clayey texture). Samples were collected at depths of 0 to 10 and 10 to 20 cm at the end of the region’s rainy season. The samples were packaged, identified and sent to the EMBRAPA Amazônia Oriental Laboratory in Belém, where enzymatic analyses of arylsulfatase and β-glucosidase were carried out. The data obtained was subjected to descriptive statistics, analysis of variance (p<0.05) and Tukey’s test (p<0.05), using SISVAR statistical software and Multivariate Principal Component Analysis (PCA) was carried out using R Software. The activity of the β-glucosidase enzyme was significantly higher in the Fazenda Novo Horizonte area, favored by the practice of no-till farming and the annual increase in organic matter, and the activity of arylsulfatase was higher in the FLONA area, stimulated by the constant deposition of organic matter from the forest. Studies are needed to elucidate the low activity of β-glucosidase in the FLONA area.